2008
DOI: 10.1016/j.jhep.2008.05.011
|View full text |Cite
|
Sign up to set email alerts
|

DNA polymorphisms and response to treatment in patients with chronic hepatitis C: Results from the HALT-C trial

Abstract: Among non-Hispanic Caucasian patients treated with peginterferon and ribavirin after failing previous treatment with interferon, homozygosity for the ACC IL10 promoter diplotype was associated with SVR.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(31 citation statements)
references
References 43 publications
1
29
0
1
Order By: Relevance
“…Some former reports have revealed that an IL-10 high production genotype/haplotype is related to reduced complete HCV clearance by IFN treatment (31)(32)(33). On the other hand, several reports that have examined various ethnic groups found no relationship between IL-10 gene polymorphisms and sustained response to IFN treatment (34)(35)(36).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some former reports have revealed that an IL-10 high production genotype/haplotype is related to reduced complete HCV clearance by IFN treatment (31)(32)(33). On the other hand, several reports that have examined various ethnic groups found no relationship between IL-10 gene polymorphisms and sustained response to IFN treatment (34)(35)(36).…”
Section: Discussionmentioning
confidence: 99%
“…For example, ribavirin administration promotes Th1 lymphocytes and suppresses IL-10 production (38). However, discrepancies still remain between the studies that have involved identical IFN treatment programs (33,36). The combinations of gene polymorphisms of other cytokines suggest that this is the key factor in association studies.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, elevated IL-10 levels are associated with a high risk of inefficient HCV clearance and resistance to IFN treatment [18][19][20][21]. Our recent study showed that low serum IL-10 levels as well as high IL-12p40 and IL-18 levels at baseline were independent predictive factors for a SVR to combination therapy [22].…”
Section: Introductionmentioning
confidence: 96%
“…Underlined HLA alleles appear in more than one study. References: (Thio, Gao et al 2002;McKiernan, Hagan et al 2004;Wang, Zheng et al 2009), (Thio, Thomas et al 2001;Yee 2004;Yoon, Han et al 2005;Ksiaa, Ayed-Jendoubi et al 2007;Harris, Sugimoto et al 2008), (Ishida, Ikebuchi et al 2011), (Falleti, Fabris et al 2010), (Haas, Weiß et al 2009), (Mueller, Mas-Marques et al 2004), (Yee, Tang et al 2001) (Morgan, Lambrecht et al 2008), (Thio, Goedert et al 2004;Paladino, Fainboim et al 2006), (Knapp, Hennig et al 2003;Lio, Caruso et al 2003;Kimura, Saito et al 2006;An, Thio et al 2008), (Schott, Witt et al 2008), (Huang, Yang et al 2007), (Ge, Fellay et al 2009;Mangia, Thompson et al 2010), (Tanaka, Nishida et al 2009;Rauch, Kutalik et al 2010), (Vejbaesya, Nonnoi et al 2011), (Khakoo, Thio et al 2004;Montes-Cano, Caro-Oleas et al 2005), (Persico, Capasso et al 2008), (Su, Yee et al 2008), (Suzuki, Arase et al 2004), (Knapp, Yee et al 2003), (Dai, Chuang et al 2010). The innate immune system has a critical role in detecting pathogens and triggering the immune response.…”
Section: Host Genetic Diversity and Natural History Of Hcv Infectionmentioning
confidence: 99%